GATA5 mutation homozygosity linked to a double outlet right ventricle phenotype in a Lebanese patient. Issue 2 (20th December 2015) - Kassab, Kameel; Hariri, Hadla; Gharibeh, Lara; Fahed, Akl C.; Zein, Manal; El‐Rassy, Inaam; Nemer, Mona; El‐Rassi, Issam; Bitar, Fadi; Nemer, Georges
Abstract : GATA proteins have been shown to play a major role in organ development and function by controlling different aspects of cell proliferation and differentiation. Mouse models with targeted genes inactivation recapitulate human congenital diseases phenotypes and genotypes with subtle variations in genetic backgrounds. We screened for mutations in the GATA5 gene that could be linked to congenital heart defects, and found novel variants and previously reported variants which, however, need to be inherited on both alleles, contrary to what has been published so far, so to be linked to the underlying phenotypes. Abstract: Background: GATA transcription factors are evolutionary conserved zinc finger proteins with multiple roles in cell differentiation/proliferation and organogenesis. GATA5 is only transiently expressed in the embryonic heart, and the inactivation of both Gata5 alleles results in a partially penetrant bicuspid aortic valve (BAV) phenotype in mice. We hypothesized that only biallelic mutations in GATA5 could be disease causing. Methods: A total of 185 patients with different forms of congenital heart disease (CHD) were screened along 150 healthy individuals for GATA4, 5, and 6 . All patients' phenotypes were diagnosed with echocardiography. Results: Sequencing results revealed eight missense variants (three of which are novel) in cases with various conotruncal and septal defects. Out of these, two were inherited in recessive forms: the p.T67P variant, which was found both in patients and in healthy individuals, and the previously described p.Y142H variant which was only found in a patient with a double outlet right ventricle (DORV). We characterized the p.Y142H variant and showed that it significantly reduced the transcriptional activity of the protein over cardiac promoters by 30–40%. Conclusion: Our results do prove that p.Y142H is associated with DORV and suggests including GATA5 as a potential gene to be screened in patients with this phenotype.